The ASEAN Export Paradox: Endogenous Resilience and Structural Transformation in Southeast Asian Trade Dynamics - Endang; Hartiningsih Astuti; Diah Chitra Puspitaningrum (Universitas Udayana, 2026)
This study analyzes relationships between ASEAN exports and key macroeconomic variables (imports, GDP current prices, GDP per capita, inflation, FDI) during 2013-2022. Few studies have discussed this relationship using a Vector Error Correction Model approach with comprehensive panel data from all ASEAN member states. Results reveal that exports exhibit high endogeneity with 98.21% of variability explained by internal dynamics. This research identifies a temporal dichotomy where imports positively affect exports in the short-term but negatively in the long-term. We observe an